MAKNA FABEL SERANGGA DALAM AL-QUR’AN MENURUT TAFSIR AL-TAHRIR WA AL-TANWIR - Rummanah Rummanah; M Ziyadulhaq; Ade Naelul Huda (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study aims to examine the meaning of insect fables in the Qur’an through the perspective of Tafsir Al-Tahrir wa Al-Tanwir. The primary focus of this research is on the stories of ants, bees, and spiders as representations of small creatures rich in educational, moral, and spiritual values. The method employed in this study is a literature review with a qualitative approach, analyzing Qur’anic verses related to insects along with the interpretations presented by Ibn ‘Āshūr in his exegesis. The findings reveal that insects in the Qur’an function not merely as narrative objects but also as instructional media containing profound messages about human life. The story of ants illustrates the importance of cooperation, leadership, and vigilance; bees reflect diligence, productivity, and environmental benefit; while spiders symbolize the fragility of structures that appear strong outwardly but are inherently weak. Tafsir Al-Tahrir wa Al-Tanwir emphasizes rationality and contextual interpretation, thereby expanding the understanding of symbolic messages within Qur’anic fables. Thus, the use of insects as fables in the Qur’an represents an effective divine pedagogical approach in conveying life values in a simple yet profound manner.